REQUEST EXPRESSION USED BY THE ENGLISH DEPARTMENT STUDENTS - Desti Handayani; Dian Susyla; Kiagus Baluqiah (Universitas Bengkulu, 2016)
In this research, the researcher wants to know what are the forms and what is the request strategy that frequently used by the English department students. The objectives of this research were to know and describe the form of request expressions used by the English department students, and also to find out what is the request strategy they used. The design of this research was descriptive method. The data were collected by using the cards, and the samples expressed the instruction based on the cards. The data were analyzed based on the category framework of request strategies proposed by Blum-Kulka et al (1989). From the three categories of request strategies written by Blum-Kulka et.al (1989), Direct level, Conventionally Indirect Level, and Non-Conventionally Indirect level. The students only used the conventionally indirect level when they expressed the request to the hearer, there were ‘can’, ‘could’, and ‘would’ that involves in query preparatory. From the result of this research, the researcher can conclude that there are some forms of request expression that used by the English Department students, such as can you, could you, and would you. From the categories of request strategies written by Blum-Kulka et.al 1989, the students only used the conventionally indirect level when they expressed the request to the hearer, there are can, could, and would.